2014
DOI: 10.1021/cb5008713
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 C-Terminal Inhibitors Exhibit Antimigratory Activity by Disrupting the Hsp90α/Aha1 Complex in PC3-MM2 Cells

Abstract: Human Hsp90 isoforms are molecular chaperones that are often up-regulated in malignances and represent a primary target for Hsp90 inhibitors undergoing clinical evaluation. Hsp90α is a stress-inducible isoform of Hsp90 that plays a significant role in apoptosis and metastasis. Though Hsp90α is secreted into the extracellular space under metastatic conditions, its role in cancer biology is poorly understood. We report that Hsp90α associates with the Aha1 co-chaperone and found this complex to localize in secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 50 publications
3
42
0
1
Order By: Relevance
“…Previously, we reported that HSP90␣ forms a complex with the late phase co-chaperone, AHA1, and that the HSP90␣-AHA1 complex is transported toward the leading edge of a migrating cell in secretory vesicles (Fig. 6A) (49). Our cell organelle fractionation studies also revealed that cytosolic HSP90␣ levels were dependent upon GRP94 (Fig.…”
Section: Grp94 Knockdown Cells Are Defective In the Transport Of Secrsupporting
confidence: 74%
See 2 more Smart Citations
“…Previously, we reported that HSP90␣ forms a complex with the late phase co-chaperone, AHA1, and that the HSP90␣-AHA1 complex is transported toward the leading edge of a migrating cell in secretory vesicles (Fig. 6A) (49). Our cell organelle fractionation studies also revealed that cytosolic HSP90␣ levels were dependent upon GRP94 (Fig.…”
Section: Grp94 Knockdown Cells Are Defective In the Transport Of Secrsupporting
confidence: 74%
“…3). To determine whether integrin molecules are dependent upon GRP94 or other HSP90 isoforms, GRP94, HSP90␣, and HSP90␤ knockdown cells were constructed (16,49). Integrin ␣L was included in the Western blotting analysis because it was previously reported to be dependent on GRP94 (11).…”
Section: Grp94 Knockdown Cells Are Defective In Filamentous Actinmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, and due to its association with Hsp90, the presence of Aha1 in exosomes (Fig. 8) comes as no surprise since Hsp90-Aha1 complexes have been shown before to be secreted by human cells via exosomes (Ghosh et al 2015;Park et al 2010).…”
Section: Aha1mentioning
confidence: 87%
“…22 Those studies indicated that the noviose sugar was responsible for binding Hsp90 while the benzamide side chain present in KU-174 ( Figure 1) interacted with Aha1, and, when combined, manifested anti-cancer activity. 22 In contrast, replacement of the benzamide with an acetamide chain, as in the case of KU-32, did not disrupt the Hsp90α/Aha1 complex and, consequently, did not exhibit anti-cancer activity. 22 In an effort to systematically investigate the differences manifested by the alkyl and aryl containing amide side chains, structure−function studies were investigated to identify the point of divergence at which a neuroprotective agent is transformed into an anti-cancer agent.…”
Section: ■ Introductionmentioning
confidence: 99%